The Role of Political Parties in Public Policy Formation: A Perspective from Political Systems Theory - Santoso, Bagus; Kurniawan, Nanang; Ramdan, Muhammad (Universitas Negeri Makassar, 2024)
Political parties play a crucial role in shaping public policy in democratic systems, influencing the governance structure and decision-making processes. In Indonesia, political parties are essential intermediaries between the state and society, bridging the gap between government institutions and the public's aspirations. This study aims to explore the role of political parties in the formulation of public policies from the perspective of Political Systems Theory. Specifically, it seeks to examine how political parties contribute to policy development, the extent of their influence, and the mechanisms through which they interact with other stakeholders. Using a qualitative research approach, data were collected through in-depth interviews with key political figures, party representatives, and policy experts, complemented by document analysis. The findings indicate that political parties in Indonesia serve as key actors in the policy formation process, though their effectiveness varies based on their alignment with government coalitions and their capacity to mobilize public support. The study also reveals that political systems theory provides a useful framework for understanding the dynamic interactions between political parties, governmental institutions, and the broader society, emphasizing the feedback loops and adaptive mechanisms that drive policy evolution. These insights contribute to a deeper understanding of the political landscape in Indonesia and the critical role that political parties play in shaping public policy.